Synergistic Antimicrobial Activity of Essential Oils and Vitamin C: Mechanisms, Molecular Targets and Therapeutic Potential - Sylvia Stamova; Neli Ermenlieva; Gabriela Tsankova; Silviya P. Nikolova; Emilia Georgieva (Applied Sciences)
Antimicrobial resistance (AMR) poses an increasing challenge to modern medicine, necessitating the search for novel therapeutic strategies. This study evaluates the synergistic antimicrobial activity of oregano essential oil (OEO) and thyme essential oil (TEO) in combination with vitamin C against clinically relevant pathogens. The antimicrobial activity was assessed using MIC, MBC and MFC assays, alongside in silico analyses utilizing Swiss Target Prediction, STRING and Reactome to identify potential molecular targets and underlying biological mechanisms. The results demonstrate that the combination of oregano oil and vitamin C significantly reduces MIC and MBC values against E. coli and C. albicans, indicating a synergistic effect, while an antagonistic interaction was observed against S. aureus. Protein interaction analysis revealed that thymol and carvacrol inhibit NF-κB and activate Nrf2, leading to the modulation of inflammatory and antioxidant responses. Additionally, carvacrol suppresses biofilm formation, while vitamin C enhances phagocytosis and the production of reactive oxygen species (ROS). These findings suggest that combining vitamin C with essential oils may serve as an effective adjuvant approach in antimicrobial therapy, particularly for infections associated with oxidative stress and chronic inflammation.